Pembuatan Briket dari Campuran Eceng Gondok (Eichhornia crassipes) dan Tongkol Jagung (Zea mays) Sebagai Sumber Bahan Bakar Alternatif - Gilar Khairul Sanatria; Deska Nurhidayat; M. Syahri (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Diminishing fossil energy due to excessive use causing problem for people. This problem should beimmediately balanced with renewable alternative energy, one example is biomass. The purpose of this studywas to create an alternative fuel in the form of briquettes from a mixture of water hyacinth and corn cobs toknow the calorific value, ash content, volatil matters, ash bound, and the water content in the briquettes witha mixture of water hyacinth (Eichohornia crassipes) and corncobs (Zea mays). Briquettes was made bymixing water hyacinth and corn cobs that have finished in the pyrolysis process using temperature 400C,500oC and 600oC with a weight ratio of 3: 2 and 3: 1. Starch was used as an adhesive with percentage 8%and 10%. The results showed that the highest value of calorific briquettes at weight ratio of 3: 2, leveladhesive 8%, and the pyrolysis temperature of 600oC with 5818.6 cal / g. In this study, it can beconcluded, if pyrolysis temperature is increasing then the content of carbon bound is increasing. Therefore,the calorific value of briquettes will be increase.